HUMAN CYTOMEGALOVIRUS INFECTION AMONG NEONATES WITH SYMPTOMATIC CONGENITAL INFECTIONS AND BIRTH DEFECTS (Iraqi Journal of Medical Sciences, 2017)
Background: Human cytomegalovirus (HCMV) is the major viral etiology of congenital infection and birth defects, during current maternal infection the fetal transmission is high (30-40%) and the symptomatic neonates have diseases involving the neurologic, hematopoietic, respiratory and other organ systems, causing high mortality and long-term sequelae.Objective: To measure the frequency of congenital and perinatal HCMV infection among symptomatic neonates and its possible burden of disease among them.Methods: A total of one hundred ninety-eight symptomatic neonates with clinical manifestations of overt congenital infection enrolled in this study from September 2014 to March 2015. Serum samples were obtained from each subject targeted in this study. HCMV infection was defined as HCMV-IgM antibody positive by Electrochemiluminescence Immunoassay (ECLIA) techniques. Results: The prevalence of HCMV infection among symptomatic neonates with congenital infection was 25 (12.6%). The average age of HCMV detection was 9.96 (SD 6.73) days with a median of 7 days, a minimum of 3 days and a maximum of 28 days. Jaundice was the most predominant clinical finding 14 (56%), followed in order of frequency by hepatomegaly 9 (36%) and pneumonitis 7 (28%).Conclusion: The high prevalence of neonatal HCMV infection among neonates with symptomatic congenital infections could indicate a high rate of maternal HCMV primary or current infection among our population.Keywords: HCMV, congenital infection, neonates, clinical finding. DOI: 10.22578/IJMS.14.4.14